Empowering Learner Agency Through Mobile-Driven Transmedia Adventures - Kurniawan, Yulius; Fadilah, Eka; Winardi, Yohanes Kurniawan (Universitas Pendidikan Ganesha, 2025)
Learner agency is a crucial factor enabling learners to make decisions and act upon them, thereby transforming their learning experiences. Identifying agency within the context of digital technology advancements, particularly through mobile-driven transmedia experiences, is essential. This study aims to examine the archetypes of learner agency in task-based activities conducted out of classroom activities. Previous research has predominantly focused on the utility of mobile devices within classroom settings, overlooking the potential benefits of agentive learning opportunities outside the classroom. This study employed a qualitative case study design grounded in Complex Dynamic System Theory (CDST) and tied to Retrodictive Qualitative Modelling (RQM) technique. Data were collected through task observations, Focus Group Interviews, and in-depth interviews. Thematic analysis was used to identify dynamic patterns and signatures related to learner agency and transmedia engagement across contexts. Thirty-five EFL learners participated in three sequential task activities using mobile phones both inside and outside the classroom. From this group, three participants were purposively selected for in-depth interviews to explore their significant experiences in completing the tasks. The findings reveal two primary types of learner agency: intentional and incidental. While intentional agency is limited by spatiotemporal constraints, incidental agency transcends these boundaries. The study's implications highlight the potential of transmedia to empower learner agency through mobile-driven technology, offering valuable insights that can enhance language teaching practices beyond traditional classroom settings.